The relationship of employer branding and career growth on talent retention in the public sector : roles of recruitment practices as mediator - Norasyikin binti Shaikh Ibrahim
Malaysian public sector today faces continuous complex transformations in a rapidly changing environment. In order to contribute towards the growth of the nation, its human capital must be developed to respond to these changes. At that juncture, Malaysian public sector needs to cultivate strategies to attract, develop and retain their talent through proper talent management and employer branding. This research investigates the relationship between employer branding with talent retention and career growth, mediated by recruitment practices. The context of this research included education, science and technology, and the medical sector of the Malaysian public service. This is due to attrition and is considered as brain drain in the Malaysian public sector. Employer branding which covers marketing and human resource management (HRM) in the public sector was less discussed and it is hoped this research will contribute to the body of knowledge. For this study, proportionate stratified sampling was employed. The respondents who represented from medical, science and technology (S&T) and education sectors were selected from each stratum of the three groups of professionals from the three sectors. The data collection for this study was carried out through self-administered questionnaires. Four hundred and fifty-two useable responses were received and further analyzed using the appropriate statistical procedures. The data collected was processed using computer software; Statistical Package for Social Science (SPSS) version 23.0 and SMART PLS 3.2.7. SPSS is used for descriptive statistics whilst Smart PLS 3.2.7 was used to validate the research model and test the proposed research hypotheses. There were seven hypotheses examined in this study. The findings conclude that there is a significant influence of employer branding and career growth towards talent retention. Furthermore, the findings partially support the hypotheses on mediating effects. Recruitment practices mediates the relationship of employer branding and career growth towards talent retention. Undoubtedly, when an organization tapped talented employees during recruitment practices more likely to report higher levels of retention.